The Graded Concentration of Bleach Solution and Material Size Plays an Important Role in the In Vitro Sterilization of Thyphonium flagelliforme Plants - Rahmadara, Gemilang; Tajuddin, Teuku; Suparjo, Suparjo; Sobir, Sobir; Dinarti, Diny; Khairiyah, Hayat (International Journal of Agriculture System, 2024)
The sterilization is a primary step in in-vitro culture. plant breeding through in-vitro culture hinges on the successful effectiveness of the sterilization method in producing sterile plants. This research aims to optimize sterilization methods using a completely randomized factorial design. The first factor is the size of the material (small and large), and the second factor is the graded concentration of the bleach solution. The study revealed that Material sizes do not have a significant effect on contamination level, all the same, large size materials increase the survival rate of sterilized rodent tuber plants. The application of graded bleach solution concentrations at 25%, 20%, and 15% is able to reduce contamination to 0% on small size materials and 5 % on large size materials. Material sizes do not have a significant effect on contamination level, all the same, large size materials increase the survival rate of sterilized rodent tuber plants.